Shared Fate of Meningeal Mast Cells and Sensory Neurons in Migraine - Koyuncu Irmak, Duygu; Kilinc, Erkan; Tore, Fatma (Frontiers in Cellular Neuroscience, 2019)
Migraine is a primary headache disorder which has complex neurogenic pathophysiological mechanisms still requiring full elucidation. The sensory nerves and meningeal mast cell couplings in the migraine target tissue are very effective interfaces between the central nervous system and immune system. These couplings fall into three categories: intimacy, cross-talk and a shared fate. Acting as immediate call-center of the neuroimmune system, mast cells have fundamental roles in migraine pathophysiology. Considerable evidence shows that neuroinflammation in the meninges is the key element resulting in the sensitization of trigeminal nociceptors. The successive events such as neuropeptide release, vasodilation, plasma protein extravasation, and mast cell degranulation that form the basic characteristics of the inflammation are believed to occur in this persistent pain state. In this regard, mast cells and sensory neurons represent both target and source of the neuropeptides that plays autocrine, paracrine, and neuro-endocrine roles during this inflammatory process. This review intends to contribute to the better understanding of the meningeal mast cell and sensory neuron bi-directional interactions from molecular, cellular, functional points of views. Considering the fact that mast cells play sine qua non role in expanding the opportunuties for targetted new migraine therapies, it is of crucial importance to explore these multi-facet interactions.